2015
DOI: 10.1094/cchem-01-15-0013-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parboiling on Milling, Physicochemical, and Textural Properties of Medium‐ and Long‐Grain Germinated Brown Rice

Abstract: Cereal Chem. 93(1):47-52Germinated brown rice is considered a more nutritious and palatable cooked product than conventional brown rice. However, germination usually decreases rice milling yield and alters some physicochemical properties. Parboiling is commonly used to increase milling yield and retain nutrients, but it also changes rice color and texture. The objective of this study was to investigate the effect of parboiling on milling, physicochemical, and textural properties of a medium-grain and a longgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(87 reference statements)
2
16
0
Order By: Relevance
“…Both treated and untreated BR split along the long axis after cooking. This is consistent with previous studies which, found both medium‐ and long‐grain germinated parboiling BR split after cooking (Han et al, ). They also reported that kernel splitting by constricting swelling on the kernel surface as the endosperm swelling during cooking.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Both treated and untreated BR split along the long axis after cooking. This is consistent with previous studies which, found both medium‐ and long‐grain germinated parboiling BR split after cooking (Han et al, ). They also reported that kernel splitting by constricting swelling on the kernel surface as the endosperm swelling during cooking.…”
Section: Resultssupporting
confidence: 94%
“…These results are consistent with earlier studies which, found that the discoloration was mainly because of maillard reaction. (Chavan et al, ; Han et al, ). Since the increased lightness of cooked BR will have a positive effect on consumer perception, FTCBR and HPPBR might be more favored than GPBR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the process of parboiling of rice, the purpose of hydration is to provide the grain moisture necessary to induce the phenomenon of gelatinization (Balbinoti, Jorge, de, & Jorge, ; Han, Jinn, Mauromoustakos, & Wang, ). The gelatinization occurs due to the combination of fundamental factors, moisture, and temperature, promoting in the grain, the irreversible collapse of hydrogen bonds between the amylose and amylopectin of starch (Buggenhout, Brijs, Celus, & Delcour, ; Oli, Ward, Adhikari, & Torley, ).…”
Section: Introductionmentioning
confidence: 99%
“…The main reactants include protein, fat and starch, especially amylose (Mohan, Malleshi, & Koseki, 2010). Amylose is readily hydrolyzed by germination‐related enzymes, such as α‐amylase, β‐amylase and α‐glucosidase (Mohan et al, 2010; Pinkaew, Naivikul, Thongngam, & Wang, 2016) and bound to other compounds such as lipid and protein, especially by heating during parboiling and drying (Han, Jinn, Mauromoustakos, & Wang, 2016; Ramesh, Bhattacharya, & Mitchell, 2000). It was noted that the amylose content is prone to be underestimated once the amylose forms complexes with other molecules (Mohan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%